The Effect Of Brand Satisfaction And Luxury Brand Attachment On Brand Loyalty In Zalora Marketplace (Study On Zalora Marketplace Consumers In Medan City) - Maharani br Aruan; Onan Marakali Siregar (UNIVED Press, 2026)
In the rapidly evolving digital marketplace landscape, understanding the drivers of brand loyalty has become crucial for e-commerce platforms, particularly those specializing in luxury fashion brands. This study examines the influence of brand satisfaction and luxury brand attachment on brand loyalty among Zalora marketplace consumers in Medan City, Indonesia. The research employed a quantitative methodology using purposive sampling technique to collect data from 100 respondents who had made purchases on Zalora marketplace at least twice. Multiple linear regression analysis was conducted using SPSS 25.0 to examine the relationships between variables. The findings reveal that brand satisfaction significantly and positively influences brand loyalty (t = 4.114, p < 0.001), with an unstandardized coefficient of 0.336 indicating a strong predictive relationship. Luxury brand attachment also demonstrates a significant positive effect on brand loyalty (t = 2.625, p = 0.010), with an unstandardized coefficient of 0.188. The combined influence of both variables on brand loyalty is statistically significant (F = 85.187, p < 0.001), with an adjusted R² of 0.630, indicating that 63% of the variance in brand loyalty is explained by brand satisfaction and luxury brand attachment collectively. The standardized coefficients reveal that brand satisfaction (β = 0.504) has a stronger influence compared to luxury brand attachment (β = 0.321). Both brand satisfaction and luxury brand attachment serve as significant predictors of brand loyalty in the luxury e-commerce marketplace context, providing valuable insights for marketplace managers and luxury brand strategists seeking to enhance customer retention and loyalty through integrated operational excellence and emotional engagement strategies.